Modern migration studies of Belarus - Zlotnikov, Anatolii G. (Journal of the Belarusian State University. Sociology, 2024)
The historiography of Belarusian migration studies is considered. A review of historical, economic, sociological, geographical, statistical, demographic, legal and political dissertations dealing with migration issues is conducted. The social problems that act as factors of migration are identified. It is noted that in recent years the number of dissertation studies on migration has decreased in Belarus. The connection between population migration and the problems of demographic development in Belarus is shown.
Keywords: migration studies; migration; migration balance; Belarus; demographic security; historiography of Belarusian migration studies; dissertation research on migration problems